A Model Example: Coexisting Superior Mesenteric Artery Syndrome and the Nutcracker Phenomenon - Rebecca Nunn; Jaimie Henry; Alistair A. P. Slesser; Rukshan Fernando; Nebil Behar (Case Reports in Surgery)
Superior mesenteric artery (SMA) syndrome is a rare cause of gastrointestinal obstruction, caused by external compression of the third part of the duodenum by the SMA. It may be associated with the Nutcracker phenomenon: external compression of the left renal vein. To our knowledge, there are few reports in the literature describing the coexistence of these two conditions and so we take this opportunity to highlight a rare cause of the acute abdomen that might otherwise be overlooked in cases of nonspecific abdominal findings and potentially unremarkable initial investigations. We report a case of SMA syndrome and Nutcracker phenomenon in a 19-year-old female who presented to our emergency department with a short history of epigastric pain and emesis. The SMA syndrome is thought to develop as the result of an abnormally narrow angle between the proximal SMA and the aorta, for which a number of predisposing factors have been described. Surgical options exist; however, the SMA syndrome is typically managed conservatively in the first instance, consistent with the approach described in this case. The Nutcracker phenomenon may give rise to the Nutcracker syndrome in the presence of typical clinical manifestations; however, these did not feature in this case.